Digital Transformation for E-learning at the Tertiary Level in Bangladesh: Prospects and Challenges - Fahmida Haque (European Scientific Journal, ESJ, 2025)
In the 21st century, Higher Education Institutions have prioritized digital shift as an apparent and essential process for their institutions. In the face of the growing importance and demands of digital incorporation into the classroom and examination process, the HEIs in Bangladesh continue to impart online education even after the pandemic. Having this backdrop, the present research aims to identify the challenges that the HEIs in Bangladesh are facing in implementing digitalization. Since the present study aims to respond to the research questions of a qualitative and quantitative nature, data collection and analysis techniques from both methodologies are implemented, and the Mixed Method Research approach has been chosen as the methodology of this research. The findings of the study show that due to digital transformation, HEIs in Bangladesh are facing a number of challenges. The major challenges are no strategic vision, policy, and legislative structure; inadequate digital literacy of all stakeholders; poor internet network; lack of outcome-based digital platform of teaching and learning; lack of digital campus network information security; financial constraints; inadequate technological support; data enablement solutions are limited; artificial intelligence is not fully functional; limited digital academic library facilities, etc. The study has proposed several suggestions to overcome the challenges. These are a strategic vision for digital transformation; modernization of the curriculum, Learning Management System (LMS), etc. It then puts forward a framework for “digital maturity” that higher education institutions (HEIs) can adopt to assess their existing digital strategies and enhance them by integrating various enterprises and methodologies.